Pengaruh Lama Perikatan KAP, Dan Fee Audit Terhadap Audit Delay Pada Perusahaan Manufaktur Sektor Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020 - 2022 - Anak Agung Ayu Putri Rahayu; Ni Wayan Yuniasih; Rai Dwi Andayani W (UNHI Press, 2025)
This research aims to empirically analyze the influence of KAP engagement length and audit fees on audit delays in manufacturing companies in various industrial sectors listed on the Indonesia Stock Exchange in 2020-2022. Data collection uses documentation by looking at audit reports of manufacturing companies in various industrial sectors listed on the IDX. The population used was 47 companies. Sampling used a purposive sampling technique to obtain a sample of 42 companies with 3 years of observation, resulting in a sample of 126 financial reports. Data analysis in this study used multiple linear regression. The research results found that the length of the KAP engagement had a negative and significant effect on audit delay, while the audit fee had a negative but not significant effect on audit delay. Suggestions that can be given to companies can reduce reporting delays by providing data to auditors quickly and comprehensively.